Evaluation of the Emergency Management Conditions Program in HSE-MS: A Case Study on a Car Dashboard Manufacturing Company (Rasti Kar Alborz) - Ali POURARJMAND; Hamed MOHAMADI (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: The aim of this study is to investigate the relationship between emergency management in the field of HSE_MS in Rastikar Alborz Dashboard Company in Qazvin province. Method: This was a descriptive study conducted with a survey approach. It was applied, in terms of purpose, and correlational, in terms of method of implementation. The statistical population of the study consisted of employees working in Rastikar Alborz Company. Based on the Chris-Morgan table, 169 people were selected as a statistical sample of the study using the relative class sampling method. In order to collect data, demographic characteristics questionnaires, researcher-made questionnaires on emergency management and safety, health and environmental management (HSE _ MS) were used. Then, they were validated by professors. Confirmation and reliability of the questionnaires were estimated to be 0.90 and 0.85, respectively, through Cronbach's alpha. Descriptive statistics (dispersion indices) and inferential statistics (Pearson correlation, linear regression) were used to analyze the data by SPSS18 software. Results: The results of the study indicated that there was a positive and significant relationship between the components of employees' level of perception of emergency management and management (HSE _ MS) {r: 0.19 and p /0 0.001}. The coefficient of regression was also equal to 0.44. Conclusion: Based on this result, the ability to predict and explain the dimensions of management (HSE _ MS) for the emergency management component is moderate, and the dimensions of management (HSE _ MS) were above average. Due to the importance of emergency management in the company and the significant role of safety, health and environmental management in this field, the authors recommend that programs such as training courses for employees be provided.